2019
DOI: 10.12669/pjms.35.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between serum vaspin levels and insulin resistance in chronic renal failure?

Abstract: Objective: Chronic kidney disease (CKD) patients have insulin secretion disorders and resistance to insulin effects, that is responsible for the development of cardiovascular events. Vaspin is an adipocytokine that regulates glucose and lipid metabolism. We aimed to determine the serum vaspin levels and its relationship with insulin resistance in CKD patients. Methods: In the study groups, serum vaspin levels, anthropometric parameters and routine blood tests were measured. The serum vaspin levels were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…The patients with solitary hypertension and combined diabetes had the most significant number of moderate interactions, followed by diabetes alone (minor DDIs). Moreover, the literature indicated that CKD patients with insulin resistance or hyperinsulinemia are more at risk of developing cardiovascular events [29]. The large number of drugs prescribed to patients with hypertension and diabetes mellitus can be attributed to beta-blockers, ACE inhibitors, hypolipidemic agents, calcium channel blockers, insulin, and anticoagulants to decrease the risk of various complications.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with solitary hypertension and combined diabetes had the most significant number of moderate interactions, followed by diabetes alone (minor DDIs). Moreover, the literature indicated that CKD patients with insulin resistance or hyperinsulinemia are more at risk of developing cardiovascular events [29]. The large number of drugs prescribed to patients with hypertension and diabetes mellitus can be attributed to beta-blockers, ACE inhibitors, hypolipidemic agents, calcium channel blockers, insulin, and anticoagulants to decrease the risk of various complications.…”
Section: Discussionmentioning
confidence: 99%
“…Increased vaspin levels have been associated to obesity and insulin sensitivity [7,26]. Many studies [27,28] contradicted these findings, demonstrating no connection between vaspin levels and insulin sensitivity or obesity.…”
Section: Discussionmentioning
confidence: 99%
“…According to reports, lipid metabolism disorders are common in CRF patients, and with the deterioration of renal function, abnormal lipid metabolism is more significant [38]. Patients with CRF have higher lipid levels than the normal population possibly due to renal excretion disorders that cause lipids to accumulate [39]. Disorders of lipid metabolism in the serum of CRF patients will aggravate kidney disease, severely damage kidney function, and 4…”
Section: Discussionmentioning
confidence: 99%